Eucalyptol, Orange Oil, and Xilodent Solubility on Three Endodontic Sealants: An in vitro Study - Mayta-Tovalino, Frank (2018)
Aim: To compare the in vitro solubility of eucalyptol, orange oil, and xilodent on three endodontic sealers based on their commercial brand and immersion time. Materials and methods: A total of 240 samples of endodontic sealants were prepared, 80 from each group: I (EndoFill®), II (EndoSeal™), and III (Sealer 26®), and then they were divided into groups of 20 based on the type of solvent, eucalyptol, orange oil, xilodent, and sodium chloride (control group), which were immersed for periods of 5 and 10 minutes; the sample was calculated through the comparison of the means . Each specimen was weighted with an analytical bascule (Ohaus, USA) before and after each immersion. Results: Comparisons were made on each group through the Student’s t test. Eucalyptol revealed a higher dissolving effect in EndoSeal™ followed by orange oil, and for xilodent at both immersion periods. It was found that there was only a statisti- cally significant difference in the group eucalyptol-EndoSeal™ in the period of immersion of 5 minutes with p = 0.033; none of the three dissolvents had the capacity of dissolving the Sealer 26® during the different immersion periods. Conclusion: The eucalyptol, orange oil, and xilodent can be used for deobturation of EndoFill® and EndoSeal™ with varia- tions on the specified times established by the manufacturer; however, the Sealer 26® was not soluble in the tested solvents.